2010
DOI: 10.1111/j.1468-1293.2010.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends over time of virological and immunological characteristics in the Swiss HIV Cohort Study*

Abstract: The long-term outcome of antiretroviral therapy (ART) is not assessed in controlled trials. We aimed to analyse trends in the population effectiveness of ART in the Swiss HIV Cohort Study over the last decade. MethodsWe analysed the odds of stably suppressed viral load (ssVL: three consecutive values o50 HIV-1 RNA copies/mL) and of CD4 cell count exceeding 500 cells/mL for each year between 2000 and 2008 in three scenarios: an open cohort; a closed cohort ignoring the influx of new participants after 2000; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
6
14
0
Order By: Relevance
“…Similar to a prior study of predictors of virologic suppression [5], we found treatment interruptions to be the strongest negatively correlated predictor of having an undetectable viral load. Of note, there was a considerable decrease in the proportion of patients with an ART interruption of greater than one month duration per calendar year.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar to a prior study of predictors of virologic suppression [5], we found treatment interruptions to be the strongest negatively correlated predictor of having an undetectable viral load. Of note, there was a considerable decrease in the proportion of patients with an ART interruption of greater than one month duration per calendar year.…”
Section: Discussionsupporting
confidence: 87%
“…We did not conduct a closed cohort analysis, however, a prior study found no difference in time trends for virologic outcomes when comparing a closed versus open cohort [5]. Our results did demonstrate a significant increase in pre-treatment CD4+ T-cell counts per calendar year for patients starting ART, which may partially account for the improving time trends in virologic and immunologic response to ART [21-24].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…COMBINED ANTIRETROVIRAL (ARV) THERAPY (ART), resulting in undetectable plasma HIV, has drastically amended HIVrelated morbidity and mortality in patients, while essentially abrogating the mucosal transmission of the AIDS virus to the uninfected partner (2,3). Yet, under effective ART or highly active ARV treatment (HAART), HIV persists as proviral DNA, forming a latent reservoir within resting memory CD4 + T cells ever since the time of primary HIV infections (4-6), recalcitrant to current antiviral therapy.…”
mentioning
confidence: 99%